Can the utility value of educational sciences be induced based on a reflection example or empirical findings—Or just somehow? - Rochnia, Michael; Gräsel, Cornelia (Frontiers in Education, 2022)
Educational sciences are a major component of German teacher education. However, student teachers often do not consider educational sciences in university courses (a profession-specific combination of educational psychology, pedagogy and sociology) as helpful for the practice of teaching. To prepare future teachers for evidence-based practice, this is a disadvantageous motivational starting point, because educational sciences offer a large amount of current and relevant findings that can have a positive impact on educational practice. Thus, it would be beneficial for student teachers to see the utility value of educational sciences. The present study attempts to encourage student teachers to perceive the utility value of educational sciences with a utility value short intervention. Utility value interventions contribute to connecting the learning content with one’s own life to foster the motivation to use scientific knowledge. A 2 × 2 quasi-experiment was conducted. Two of the four groups received a utility value short intervention about educational sciences (Factor 1). In addition, a second factor was analyzed that takes up two patterns of educational reasoning in teacher education (Factor 2): Reasoning was either exemplified with an instruction to reflect on the usefulness of educational sciences (like in reflection-oriented educational reasoning) or with exemplary empirical findings from educational sciences (like in evidence-based educational reasoning). These two kinds of reasoning are objectives of teacher education and therefore could influence the effect of a utility value short intervention. Since epistemic goals influence engagement with educational sciences, they are also taken into account. The results showed that all four variants of the treatment increased the students’ assessment of the utility value of educational sciences; the utility value intervention had no additional effect. This is discussed with recourse to motivational theories and concepts of teacher education.